Analytical and Experimental Analysis of the High Pressure Boiler Feed Pump. (2016) - Tiwari, Nilesh; Kumar, Krishna; Kumar, Devranjan
Abstract: The present works discuss the comparison between the analytical and experimental performance curve of the high pressure boiler feed pump - a multistage centrifugal pump. The hydraulic loss model stated by J.F. Gulich is widely used for the analytical performance prediction of the single stage centrifugal pumps. In the present work, this methodology is implemented for the analytical performance prediction of the 10-stage industrial centrifugal pump. The given pump is installed as HPBFP (High Pressure Boiler Feed Pump) to carry water from the deaerator to boiler. The H-Q (Head versus Discharge) analytical performance characteristics curve of the pump is compared with the experimental performance characteristics curve. The deviation between the analytical and experimental curve is between 2-13% for the discussed range of discharge. This deviation is due to the assumption of the single dimensional geometry of the different components of the centrifugal pump.